Potato protease inhibitors, a functional food material with antioxidant and anticancer potential - Yaotong Liu; Yuanyuan Bian; Yan Bai; Siqi Yu; Yuxuan Tian; Jie Li; Suhong Li; Tuoping Li (Food Science and Human Wellness, 2023)
Potato protease inhibitors (PPIs), as the main component of potato protein isolate, have good safety, nutrition and great market potential. The antioxidant and anticancer properties of PPIs were evaluated with cell-based biological assays. The results showed that when the concentration of PPIs was 5 mg/mL, the peroxyl radical scavenging value was (2119 ± 204) mg VCE/100 g, and the cellular antioxidant activity values were (45.83 ± 3.5) (no PBS wash) and (33.25 ± 4.4) µmol QE/100 g (PBS wash). Cells pretreated with PPIs could significantly prevent the oxidative damage induced by H2O2, inhibit the morphological changes of cells and maintain the integrity. Furthermore, PPIs had selective anti-proliferative effects on GIST882 cells (IC50 = (10.53 ± 3.87) mg/mL) and demonstrated potent inhibition of the growth, migration and invasion of cancer cells. These findings provide a scientific basis for PPIs as promising candidates for functional foods to aid in the prevention of oxidative damage and cancer.